基于伪刚体模型的柔性铰链机构自由度分析 - 辛礼兵 (Jixie Chuandong, 2011)
Through the development in the past 20 years,the flexible mechanism has become a important branch of modern mechanisms and is widely applied in such fields as precision engineering and robotics.A flexible mechanism is a new mechanism which uses the elastic deformation of its flexible elements to transfer movement,force,or energy.The use of flexible members always makes it difficult to distinguish joints from links,which causes that the concept of degree of freedom for flexible mechanisms is different from that of rigid-body mechanisms.Based on Pseudo-rigid-body model,the definition of the two degree of freedom of a flexible mechanism and relevant corollaries are given,and calculation method of degree of freedom for flexible mechanism is analyzed.